Increased risk of lymphoma among inflammatory bowel disease patients treated with azathioprine and 6-mercaptopurine. Issue 8 (11th July 2005) - Kandiel, A; Fraser, A G; Korelitz, B I; Brensinger, C; Lewis, J D
Abstract : Background: Inflammatory bowel disease (IBD) is commonly treated with immunomodulators such as azathioprine and 6-mercaptopurine (6-MP). Studies examining lymphoma risk in IBD patients treated with these medications have been underpowered and have yielded conflicting conclusions. Aims: The purpose of this meta-analysis was to provide a more precise estimate of the relative risk of lymphoma among IBD patients treated with azathioprine or 6-MP. Methods: Studies were included if they were English language, full article, cohort studies specifically designed to evaluate cancer as an adverse outcome of treatment with azathioprine or 6-MP. Pooled standardised incidence ratios were calculated to estimate the relative risk of lymphoma associated with therapy. Heterogeneity was assessed using Poisson regression. Sensitivity analyses examined the influence of individual studies on risk estimate and heterogeneity statistics. Results: Six studies were identified that met our inclusion criteria. When the data were combined across all studies, the pooled relative risk was 4.18 (95% confidence interval 2.07–7.51; 11 observed cases, 2.63 expected). Sensitivity analysis showed that exclusion of any one study had a relatively small effect on the pooled relative risk estimate (range 3.49–5.21) but excluding either the study with the highest or lowest estimated relative risk eliminated the statistically significant heterogeneity. Conclusions: Our data suggest an approximate fourfold increased risk of lymphoma in IBD patients treated with azathioprine/6-MP. The increased risk of lymphoma could be a result of the medications, the severity of the underlying disease, or a combination of the two.